Comparative Study of Halal Certification Mechanism: Indonesia, Malaysia and Mexico - Faiqoh, Faiz Nur; Fatwa, Nur (UI Scholars Hub, 2024)
This research was conducted to examine the handling and procedures for halal certification at halal certification institution in Indonesia, Malaysia as a Muslim-majority country and Mexico as a Muslim-minority country, and to analyze using the SWOT approach. Halal product certification in Indonesia is carried out by the Halal Product Guarantee Agency (BPJPH) under the auspices of the government (Ministry of Religion). The aim is to provide guarantees to the community, especially Muslims from the products consumed. And in Malaysia it is carried out by JAKIM (Department of Islamic Development Malaysia) under the post of prime minister of Malaysia. While in Mexico it is carried out by private/independent non-governmental organizations. These three institutions have the same goal, to provide halal security and certainty to the Muslim community in the two countries in consuming food products and at a minimum. This study uses the literature study method by utilizing a variety of literature that helps explain the problems that are the focus of the study. The results of the study explain that the mechanism of implementing halal certification in Indonesia, Malaysia and Mexico has similarities. The countries of Indonesia and Malaysia are under the auspices of the government, while they are carried out by private institutions and have the challenge of a lack of human resources that meet the requirements because the country is a Muslim minority. They have differences in terms of costs, the length of the certification process, the role of the government and the sector being certified.